Resepsi Ayat Al-Qur’an dalam Tradisi Nyadran di Desa Klino Kecamatan Sekar Kabupaten Bojonegoro - Ahmad Yahya; Samani Samani; Fikih Umam Ubaidillah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT This study examines the community's reception of Quranic verses in Klino Village, Sekar District, Bojonegoro Regency, within the Nyadran tradition, as well as the Quranic values ​​integrated within it. Using the Living Quran approach, this study examines how the Quranic text is not only understood normatively but also lived and internalized in local cultural practices, such as the Nyadran tradition. The study employed qualitative methods with a phenomenological approach through observation, interviews, and documentation of Nyadran activities, which were then analyzed using content analysis. The results show that the community interprets Nyadran as a form of worship and respect grounded in Islamic spiritual values. The recitation of Surah Yasin, the tahlil prayer, and the tumpeng symbol are interpreted as expressions of gratitude and strengthening shared spirituality. The Nyadran tradition reflects Quranic values ​​such as brotherhood, gratitude, reverence, and social concern. Thus, this tradition is not just a cultural practice, but a real representation of the Living Qur'an which harmonizes Islamic values ​​and local wisdom in people's lives. Keywords : The Living Qur’an, Nyadran, The Values of the Qur’an